Giant Cell Tumor of Bone Involving the Temporomandibular Joint and Temporal Bone - Akyigit, Abdulvahap; Karlidag, Turgut; Sakallioglu, Oner; Polat, Cahit; Keles, Erol (Lippincott Williams & Wilkins, 2014)
Giant cell tumor is a primary bone tumor that usually originates from the epiphysis of the long bones and is rarely seen in the cranial region. Most frequently, the tumor develops in the sphenoid and temporal bones in the middle cranial fossa. Giant cell tumor generally shows diversity with respect to benignity, local invasiveness, and histology. Although surgical excision with negative surgical margin may lead to cure, adjuvant radiotherapy is still debated. The patient was admitted with a humming in the left ear and hearing loss. After radiologic examination, a mass with temporomandibular joint involvement as well as temporal and sphenoid bone localization was detected. The patient was diagnosed with giant cell tumor after a biopsy specimen was taken from the mass extending to the middle ear and destroying the temporomandibular joint. The current study reviewed the patient's clinical features, diagnosis, and treatment in light of the literature.
Keywords: Giant cell tumor; temporal bone; temporomandibular joint